2006
DOI: 10.1111/j.1095-8649.2006.01151.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and somatic growth on otolith growth: the discrepancy between two clupeid species from a similar environment

Abstract: Otolith growth rates of the early life stages of herring Clupea harengus (n ¼ 472) and smelt Osmerus eperlanus (n ¼ 348) collected in the Vistula Lagoon (Baltic Sea) during 1997-1999 were analysed. The larvae and early juveniles were not only collected in the same geographical area they were also of the same size (range 15-43 mm standard length, L S ), similar ages and were collected during the same seasons (May to July). Although the two clupeid species experienced very similar environmental conditions, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 46 publications
5
42
0
4
Order By: Relevance
“…It was suggested by Mosegard et al (1988) that the acceleration of otolith size is increased in higher temperature as a result of increased metabolic rate, especially if the temperature increases above optimum value for growth. For example, increase of temperature above optimum in shallow and warm waters of Vistula Lagoon was a reason of decoupling observed for Baltic herring otolith growth dependence on temperature (Fey 2005(Fey , 2006. However, this hypothesis about overoptimal temperature Otolith growth of larval menhaden 219 Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It was suggested by Mosegard et al (1988) that the acceleration of otolith size is increased in higher temperature as a result of increased metabolic rate, especially if the temperature increases above optimum value for growth. For example, increase of temperature above optimum in shallow and warm waters of Vistula Lagoon was a reason of decoupling observed for Baltic herring otolith growth dependence on temperature (Fey 2005(Fey , 2006. However, this hypothesis about overoptimal temperature Otolith growth of larval menhaden 219 Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Results of the above studies are in agreement with the main conclusion of the current research-otolith growth dependence on somatic growth-and support the value of using otoliths in somatic growth analysis Despite the evidence supporting the existence of a significant relation between fish growth and otolith growth, species-or environment-related differences can be expected. For example, Fey (2006) showed that the same environmental conditions (temperature and zooplankton) affect otolith growth differently in two co-occurring pelagic species, European smelt, Osmerus eperlanus (L.), and Atlantic herring, Clupea harengus L. For smelt, Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of several studies suggest, however, that, at least in some species, direct coupling does not occur, with, for example, otoliths continuing to grow after growth in body size has largely or entirely ceased and sometimes respond to environmental factors in different ways than body size (e.g. Fey, 2006;Wilson et al, 2009;Réveillac et al, 2015).…”
mentioning
confidence: 99%